Implementation of the Outdoor Learning Method in Social Science Subjects at Asa Cendekia Junior High School - Lailiyah, Faizzatul; Nurul Islami, Novita (Universitas Terbuka, 2025)
This study aims to describe the implementation of the outdoor learning method in Social Studies (IPS) at SMP Asa Cendekia, focusing on its planning, execution, and evaluation. A qualitative case study approach was employed, with data collected through semi-structured interviews and documentation. The research subjects included the principal, curriculum coordinator, IPS teachers, and students. The findings reveal that outdoor learning was implemented in three main stages: planning (developing teaching modules and selecting locations), execution (direct observation, group discussions, and presentations), and evaluation (student reflection and assessment of their work). The method effectively enhanced students' motivation, active participation, and contextual understanding of IPS topics. The main challenge was adapting to regulations limiting off-campus activities, but the school successfully utilized its immediate environment as an alternative. This study highlights outdoor learning as an innovative approach aligned with the principles of the Merdeka Curriculum.